2009
DOI: 10.1038/nchembio.182
|View full text |Cite
|
Sign up to set email alerts
|

A glycopeptide regulating stem cell fate in Arabidopsis thaliana

Abstract: The secreted peptide gene CLAVATA3 (CLV3) regulates stem cell fate in the shoot apical meristem in Arabidopsis thaliana plants, but the molecular structure of the active mature CLV3 peptide is controversial. Here, using nano-LC-MS/MS analysis of apoplastic peptides of A. thaliana plants overexpressing CLV3, we show that CLV3 is a 13-amino-acid arabinosylated glycopeptide. Post-translational arabinosylation of CLV3 is critical for its biological activity and high-affinity binding to its receptor CLV1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
410
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 377 publications
(436 citation statements)
references
References 15 publications
8
410
1
4
Order By: Relevance
“…This finding further supports the physiological importance of Hyp-arabinosylation in peptide signalling. Initial studies in Arabidopsis reported that arabinosylation of CLV3 glycopeptide considerably enhances its binding to CLV1 receptor kinase 26 . A recent conformational analysis of [Ara 3 ]CLV3 showed that the arabinose chain of [Ara 3 ]CLV3 extends towards the C-terminal end of the peptide and causes distinct distortion in the C-terminal half of the peptide in a highly directional manner 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding further supports the physiological importance of Hyp-arabinosylation in peptide signalling. Initial studies in Arabidopsis reported that arabinosylation of CLV3 glycopeptide considerably enhances its binding to CLV1 receptor kinase 26 . A recent conformational analysis of [Ara 3 ]CLV3 showed that the arabinose chain of [Ara 3 ]CLV3 extends towards the C-terminal end of the peptide and causes distinct distortion in the C-terminal half of the peptide in a highly directional manner 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting T3 plants (10 days after germination, DAG) were subjected to whole-plant submerged culture in 200 ml medium 24 . Secreted peptides accumulating after 24 days of culture were extracted by o-chlorophenol and fractionated in a gel-filtration column 24,26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) (Kondo et al 2006;DeYoung and Clark 2008;Miwa et al 2008;Müller et al 2008;Ohyama et al 2009;Guo et al 2010;Kinoshita et al 2010;Betsuyaku et al 2011;Lee et al 2011). Among these receptors, the LRR domains for ligand perception or the PK domains for cellular signaling are more closely related between CLV1 and FLS2 than between CLV1 and CLV2 or RPK2 (Fig.…”
Section: Common Origins Of Receptor Kinases In Immunity and Developmentmentioning
confidence: 99%
“…CLV1 is the major receptor-like kinase for CLV3 signaling and is shown to interact specifically with CLV3 in vitro. [1][2][3] CLV2, a receptor-like protein, associates with CORYNE (CRN)/SUPPRESSOR OF LLP1 2 (SOL2), a membrane associated protein pseudo-kinase with a short extracellular domain. [4][5][6] RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2) is another receptor-like kinase that is essential for CLV3 signaling.…”
mentioning
confidence: 99%